Polycarbonate/antibacterial blend nanocomposites in material extrusion 3D printing: Thermomechanical response, rheology, and biocidal metrics - Markos Petousis; Nektarios K. Nasikas; Vassilis Papadakis; Maria Spyridaki; Evangelos Sfakiotakis; Amalia Moutsopoulou; Apostolos Argyros; Evgenia Dimitriou; Nikolaos Michailidis; Nectarios Vidakis (Biomedical Engineering Advances)
The motivation of the research was to introduce nanocomposites with the polycarbonate (PC) thermoplastic as the matrix material, with biocidal capabilities and improved mechanical performance for the material extrusion (MEX) additive manufacturing (AM) technique. Such nanocomposites have not been investigated so far. They would exploit the use of the PC thermoplastic and the MEX AM method in various types of applications with respective specifications, such as in the defense or security sector, in which PC is a popular thermoplastic already. We successfully synthesized a series of PC/antibacterial nanocomposites for the material extrusion 3D printing technique. The PC/antibacterial nanocomposites consisted of 2wt. % antibacterial nanopowder intervals (2–12wt. %). The as-prepared PC/antibacterial nanocomposite batches were converted into filaments and afterward 3D printed. The 3D printed materials were subjected to a series of experimental tests to determine their mechanical, thermal, rheological, physicochemical, morphological, structural, and biocidal properties, following the respective standards. The biocidal characterization of the various PC/antibacterial nanocomposites (agar well diffusion method, Mcfarland protocol) provided evidence that both the enhanced mechanical properties (29.1 % improvement of the tensile strength with 4 wt. % nanopowder loading) and biocidal activity (gram-positive Staphylococcus aureus and gram-negative Escherichia coli were tested) of the 3D printed PC/antibacterial nanocomposites are feasible. We have concluded that the maximization of the above-mentioned multifunctionalities can be achieved for moderate loadings of antibacterial nanopowder while the 3D printing of such PC/Antibacterial nanocomposites produces high-quality parts which can find important applications in the Defence and Security domain but also “dual – use” applications in the civil domain.